A Delphi Study to Identify Indicators of Poorly Managed Pain for Pediatric Postoperative and Procedural Pain - Alison M Twycross; Jill MacLaren Chorney; Patrick J McGrath; G Allen Finley; Darlene M Boliver; Katherine A Mifflin (Pain Research and Management)
BACKGROUND: Adverse health care events are injuries occurring as a result of patient care. Significant acute pain is often caused by medical and surgical procedures in children, and it has been argued that undermanaged pain should be considered to be an adverse event. Indicators are often used to identify other potential adverse events. There are currently no validated indicators for undertreated pediatric pain.